2009
DOI: 10.1007/s00122-009-1045-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and peculiarity of annual wild soybean (G. soja Sieb. et Zucc.) from various eco-regions in China

Abstract: Annual wild soybean (Glycine soja Sieb. et Zucc.) is believed to be a potential gene source for future soybean improvement in coping with the world climate change for food security. To evaluate the wild soybean genetic diversity and differentiation, we analyzed allelic profiles at 60 simple-sequence repeat (SSR) loci and variation of eight morph-biological traits of a representative sample with 196 accessions from the natural growing area in China. For comparison, a representative sample with 200 landraces of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 22 publications
7
74
3
4
Order By: Relevance
“…These results suggest that wild soybeans collected from the Dongying region of China contained abundant genetic diversity, both at the species and population levels. However, the expected heterozygosity (H E ) and Shannon's information index (I) in this study were lower than those reported in previous studies (Wen et al, 2009;Xu and Li, 2011). The origin of the samples could partly account for these differences.…”
Section: Genetic Diversitycontrasting
confidence: 90%
“…These results suggest that wild soybeans collected from the Dongying region of China contained abundant genetic diversity, both at the species and population levels. However, the expected heterozygosity (H E ) and Shannon's information index (I) in this study were lower than those reported in previous studies (Wen et al, 2009;Xu and Li, 2011). The origin of the samples could partly account for these differences.…”
Section: Genetic Diversitycontrasting
confidence: 90%
“…Although B. yuanmingense nodulating various legumes has been found in several continents, the biovar nodulating soybeans has so far been found only in Asia (2,3,5,50). The observed high diversity of soybeannodulating Bradyrhizobium in Asia is consistent with the presence of wild soybeans and the long history of soybean cultivation in this region (51,52).…”
Section: Resultsmentioning
confidence: 56%
“…Pola pita hasil elektroforesis sampel kedelai introduksi pada gel poliakrilamid 8% yang diamplifikasi menggunakan marka A) GMES3515 dan B) Satt288 (Keterangan: M: DNA Ladder 100 bp). Laboratorium Biologi Molekuler BB Biogen, Januari-Maret 2016 yang berasal dari berbagai negara dengan agroekosistem yang sangat berbeda, sejalan dengan hasil analisis sebelumnya walaupun kultivar yang digunakan berbeda (Zhou et al, 2002;Kuroda et al, 2009;Wen et al, 2009;Kumawat et al, 2015). Hasil analisis keragaman genetik kultivar kedelai pada peneltian ini dapat menjadi dasar dalam karakterisasi plasma nutfah kedelai yang ada dan memberi informasi tentang pemanfaatan dan seleksi pada program pemuliaan kedelai ke depan.…”
Section: Analisis Filogenetikunclassified